Forecasting model for production volume and sales of red tilapia: A case study on Pertubuhan Peladang Kawasan Engkilili/Lubok Antu/ Awang Mentali Awg. Mohd. Sulaiman… [et.al.] - Awg. Mohd. Sulaiman, Awang Mentali; William, Bobby; Haji Nahar, Hawa; Abang, Hj. Morshidi; James Jabing, Luke Sakalai; Yahya, Siti Aida Rosmaryanti (2003)
The EMBA 03 team consisting ofsix- (6) students proposes a strategic planning project aimed at improving the supply chain at PPKELA. The proposal has been undertaken in respond to a request by PPKELA as a result oflarge stock of costly inventories that is kept and uncertainty of sales (actual demand). By forecasting the production and sales volume it is possible to provide the organisation a mean to determine the economic volume of production and also to improve on their sale profit. This paper is aimed to present a model for PPKELA in their social obligation in assisting the local farmers.